Can I Influence You? Development of a Scale to Measure Perceived Persuasiveness and Two Studies Showing the Use of the Scale - Thomas, Rosemary J.; Masthoff, Judith; Oren, Nir (Frontiers in Artificial Intelligence, 2019)
In this paper, we develop and validate a scale to measure the perceived persuasiveness of messages to be used in digital behaviour interventions. A literature review is conducted to inspire the initial scale items. The scale is developed using Exploratory and Confirmatory Factor Analysis on the data from a study with 249 ratings of healthy eating messages. The construct validity of the scale is established using ratings of 573 email security messages. Using the data from the two studies, we also show the usefulness of the scale, by analysing the perceived persuasiveness of different messages types on the developed scale factors in both the healthy eating and email security domains. The results of our studies also show that the persuasiveness of message types is domain dependent and that when studying the persuasiveness of message types the finer-grained argumentation schemes need to be considered and not just Cialdini's principles.